Perbeedaan Tingkat Kelelahan Antara Shift Pagi, Sore Dan Malam Pada Perawat Rawat Inap Di RS PKU Aisyiyah Boyolali - Fatona, Lusi, Tarwaka, PGDip Sc, M.Erg, Kusuma Estu Werdani, SKM., M.Kes (2015)
Hospital provides the health care facilities that operate 24 hours. The high of responbility and workload of the nurses should be cared by dividing the shift of work, namely Morning shift, Afternoon Shift, and Evening shift. This condition could give negative impact which one is fatigue. The purpose of this research is to know the difference of fatigue level at work on the shift of inpatient nurses in the hospital of PKU Aisyiyah Boyolali. The type of this research is observational analytic with cross sectonal approach. The sample in this research is the total population ammounted to 48 people. The data is obtained by stuffing the data sheet ID and measuring the fatigue level by using KAUKP2 questionnaire. Measurement of the degree of fatigue data analized by using statistical tests of Kruskal Wallis. The results of this study, show that the highest rank on the night shift = 31,82 and p-value=0,038, it means there is a difference in fatigue level of work shift in the morning, aftrenoon and evening on inpatient nurses in PKU Aisyiyah Boyolali. Recomended for the hospital to share equally work haours per shift (8hours) it is.